2020
DOI: 10.1007/s00775-020-01798-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, cellular localization and photophysical properties of Re(I) tricarbonyl complexes bound to cysteine and its derivatives

Abstract: The potential chemotherapeutic properties coupled to photochemical transitions make the family of fac-[Re(CO) 3 (N,N) X] 0/+ (N,N = a bidentate diimine such as 2,2′-bipyridine (bpy); X = halide, H 2 O, pyridine derivatives, PR 3 , etc.) complexes of special interest. We have investigated reactions of the aqua complex fac-[Re(CO) 3 (bpy)(H 2 O)](CF 3 SO 3) (1) with potential anticancer activity with the amino acid l-cysteine (H 2 Cys), and its derivative N-acetyl-l-cysteine (H 2 NAC), as well as the tripeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…The interaction of the chloride ( 1 ) and aqua ( 22 ) Re I tricarbonyl complex with amino acids containing cationic (N α ‐ p ‐tosyl‐L‐arginine methyl ester, L‐histidine methyl ester, L‐lysine methyl ester), anionic (N α ‐ tert ‐butoxycarbonyl‐L‐aspartic acid tert ‐butyl ester), polar (L‐serine methyl ester, L‐asparagine tert ‐butyl ester), and sulphur (L‐cysteine methyl ester, L‐methionine methyl ester) side chains was investigated (Figure 4) using equimolar amounts of metal complex and amino acid. Previous studies have indicated that Re I tricarbonyl complexes are able to react with Cys derivatives [47, 49, 50] and a crystal structure has revealed that the Cys is covalently bound in axial position [49] …”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the chloride ( 1 ) and aqua ( 22 ) Re I tricarbonyl complex with amino acids containing cationic (N α ‐ p ‐tosyl‐L‐arginine methyl ester, L‐histidine methyl ester, L‐lysine methyl ester), anionic (N α ‐ tert ‐butoxycarbonyl‐L‐aspartic acid tert ‐butyl ester), polar (L‐serine methyl ester, L‐asparagine tert ‐butyl ester), and sulphur (L‐cysteine methyl ester, L‐methionine methyl ester) side chains was investigated (Figure 4) using equimolar amounts of metal complex and amino acid. Previous studies have indicated that Re I tricarbonyl complexes are able to react with Cys derivatives [47, 49, 50] and a crystal structure has revealed that the Cys is covalently bound in axial position [49] …”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity of compounds 1, 2 and cisplatin were assessed with the MDA-MB-231 breast cancer cell line using the alamarBlue cell viability assay and IC50 values were determined (Table 1); we previously discussed the data for 1 and cisplatin. 46 The results showed greater cytotoxicity for complex 1 (IC50 = 38 ± 6 μM) at 24 h, compared to both cisplatin and 2 (IC50 >100 μM) over the same time period. After 48 h the IC50 of 1 decreased to 26 ± 3 μM, whereas cisplatin was 11 ± 2 μM.…”
Section: Cytotoxicity and Cellular Localizationmentioning
confidence: 87%
“…47 fac-[Re(CO)3(bpy)(H2O)](CF3SO3) (1) was prepared from fac-[Re(CO)3(bpy)Cl] as previously described. 46,48,49 Cell culture. MDA-MB-231 breast cancer cells (American Type Culture Collection; ATCC) were genetically validated and used within 6 months of testing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations